“SAKSHAM”: A Government Process Reengineered Model for Scholarship and Feereimbursement and its Impact on Society (A study of Uttar Pradesh, the most populous state of India) - Gupta, Dr. Saurabh; Rajan, Sameer (IJRDO- Journal of Educational Research, 2017)
Government executes various schemes to uplift the weaker section of the society. Scholarship disbursement and Fee reimbursement is one of the major schemes which assure that money is not a constraint for credible students aspiring for higher studies and professional courses. The scheme also assures the upliftment of downtrodden students and put them in main stream of society. SAKSHAM-eScholarship portal is the concept of electronic transfer of scholarship and fee reimbursements to the students directly into their bank accounts which enables and empowers students of weaker section of the society with education. This paper explores the various aspects of Government Process Reengineering Model “SAKSHAM” which has been adopted by the Government to interact, interface and transact with all the concerned stakeholders in a integrated and interoperable manner for disbursement of scholarship and fee reimbursement in transparent, time bound, effective and efficient manner, directly into the bank account of downtrodden students. The objective of the project is not to generate revenue however it saves a lot of revenue indirectly by minimizing the leakage of funds.